The effect of spices on carboxymethyllyinse levels in biscuits - Dunn, Jennifer (Kansas State University, 2012)
Carboxymethyllysine (CML) and other advanced glycation end products (AGEs) have been shown to affect diseases such as diabetes, cancer, and Alzheimer’s by inducing oxidative stress, inflammation, and tissue damage. CML is formed in foods through Maillard browning reactions and through various mechanisms that are affected by time, temperature, pH, water activity, trace metals, and antioxidants. Natural antioxidants can be found in plant and fruit extracts, as well as in spices. The research contained herein is in two parts. The first part includes preliminary work, which examines the percent recovery of CML from various solid phase extraction columns, the analysis of CML in maple syrup, barbeque sauce, honey, and infant formula. The data show that solid phase extraction with a C-18 cartridge produced the highest percent recovery when using a CML standard at 100 ppb, with a recovery of 69%. Furthermore, the analysis of the syrups and sauces is inconclusive, due to the very low levels of CML detected in the infant formula, and the complications due to the high levels of reducing sugars. The second part of the research examines the effect that cinnamon, onion, garlic, black pepper, and rosemary have on CML levels in biscuits. The data show that all of the spices inhibit the formation of CML, at each of the 0.5%, 1%, and 2% levels used in the experiment, by a minimum of 3% in 2% onion samples and a maximum of 79% in 0.5% cinnamon samples when looking at the cumulative data. When looking subsets of the data, the CML inhibition was a minimum of 59% in 2% onion samples and a maximum of 74% in 0.5% cinnamon samples. Other trends can be observed in the chroma values in the CML color data, which suggest that chroma values decrease as the spice level increases, but these are not statistically significant. They may be due to color from the spices themselves, or to the chemical changes in the Maillard reaction.
Keywords: Maillard browning, spices, food chemistry, AGEs; Spices; Food chemistry; AGEs; Agriculture, General (0473); Chemistry, Agricultural (0749); Food Science (0359)